2011
DOI: 10.1186/1476-511x-10-98
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of dietary canola and soybean oil intake on oxidative stress in stroke-prone spontaneously hypertensive rats

Abstract: BackgroundCanola oil shortens the life span of stroke-prone spontaneously hypertensive (SHRSP) rats compared with rats fed soybean oil when given as the sole dietary lipid source. One possible mechanism leading to the damage and deterioration of organs due to canola oil ingestion is oxidative stress. This study investigated the effect of canola oil intake on oxidative stress in this animal model.MethodMale SHRSP rats, were fed a defatted control diet containing 10% wt/wt soybean oil or a defatted treatment die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 37 publications
8
23
0
Order By: Relevance
“…Our recent study strengthened this finding, and showed that canola oil ingestion reduced the lifespan of SHRSP rats compared to soybean oil following 1% NaCl loading, 85.8 ± 1.1 and 98.3 ± 3.4 days, respectively [8]. …”
Section: Introductionmentioning
confidence: 56%
“…Our recent study strengthened this finding, and showed that canola oil ingestion reduced the lifespan of SHRSP rats compared to soybean oil following 1% NaCl loading, 85.8 ± 1.1 and 98.3 ± 3.4 days, respectively [8]. …”
Section: Introductionmentioning
confidence: 56%
“…We have previously reported that the SHRSP offspring of protein-restricted dams showed enhanced salt sensitivity, together with a rapid increase in blood pressure and a shortened lifespan. 5) In terms of the relationship between salt loading and oxidative stress, Papazzo et al 22) have reported that the GSH-Px activity in red blood cells and the malondialdehyde levels in red blood cells and plasma were greater in SHRSP fed a diet containing canola oil and high salt than in SHRSP fed a diet containing canola oil lacking salt. These results indicate that ROS and lipid peroxidation were involved in worsening of the vascular dysfunction and/or the injury induced by salt loading in SHRSP.…”
Section: Discussionmentioning
confidence: 99%
“…This data is consistent with our lifespan study data, where we showed a decrease in RBC SOD and catalase, however, RBC GPx was also reduced at the end of life. [7] Furthermore, the results from the previous lifespan study did not find any changes in the activities of the RBC antioxidants in the soybean oil group. [7] RBCs are under constant exposure to ROS and oxidative stress due to their role in transporting oxygen and carbon dioxide, and their increased content of heme iron.…”
Section: Antioxidant Enzymes and Oxidative Damagementioning
confidence: 73%
“…[7] Furthermore, the results from the previous lifespan study did not find any changes in the activities of the RBC antioxidants in the soybean oil group. [7] RBCs are under constant exposure to ROS and oxidative stress due to their role in transporting oxygen and carbon dioxide, and their increased content of heme iron. [20] Therefore, the oxidative/antioxidant balance can become altered.…”
Section: Antioxidant Enzymes and Oxidative Damagementioning
confidence: 73%
See 1 more Smart Citation